Comparison of liver function and safety in hepatocellular cancer patients treated with DEB-TACE and cTACE: a multi-center, retrospective cohort study - Xiang, Hua; Xiong, Bin; Li, Haiping; Zhao, Chang; Zhang, Zishu; Ma, Cong; Zheng, Chuansheng; Luo, Chao; Qiu, Huaiming; Yao, Yuanhui; Hu, Hongyao; Zhao, Hui; et al. (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Background: This study aimed to compare the live function change and adverse events (AEs) between drug-eluting beads (DEB) transarterial chemoembolization (TACE) with CalliSpheres® microspheres (CSM) and conventional TACE (cTACE) in treating hepatocellular carcinoma (HCC) patients. Methods: Three hundred and thirty-five HCC patients underwent DEB-TACE with CSM (n=171, DEB-TACE group) or cTACE (n=164, cTACE group) were consecutively enrolled in this multi-center, retrospective cohort study. Liver function indexes were reviewed before treatment (W0), at 1 week (W1) and 1 month (M1) post treatment. Moreover, AEs during operation and hospitalization were retrieved as well. Results: The changes of albumin (ALB) [–3.55 (–6.25 to –0.43) vs. –2.20 (–4.63–0.00), P=0.043] and total protein (TP) [–4.62 (–10.18–0.43) vs. –2.50 (–7.08–1.08), P=0.013] from W1 to W0 were lower in DEB-TACE group compared to cTACE group, while no difference was observed referring to the change of alanine aminotransferase (ALT) (P=0.494), aspartate aminotransferase (AST) (P=0.747), alkaline phosphatase (ALP) (P=0.895), total bilirubin (TBIL) (P=0.059), total bile acid (TBA) (P=0.491) from W1 to W0. And the changes of these seven indexes from M1 to W0 were all similar between DEB-TACE group and cTACE group (all P>0.05). Besides, the occurrence of pain during treatment (19.3% vs. 11.0%, P=0.034) and the occurrence of fever during hospitalization (18.1% vs. 9.1%, P=0.017) were both increased in DEB-TACE group compared to cTACE group. Conclusions: DEB-TACE with CSM is non-inferior to cTACE in terms of liver function change, while DEB-TACE with CSM leads to higher incidences of pain and fever.